Gut microbiota-derived metabolites and chronic inflammatory diseases - Alejandra Vargas; Benjamin L. Robinson; Kevin Houston; Ana Rosa Vilela Sangay; Michael Saadeh; Steve D’Souza; David A. Johnson (Exploration of Medicine)
The gut microbiota, a complex ecosystem of microorganisms, plays an essential role in maintaining immune and metabolic homeostasis. Disruption of this microbial balance, known as dysbiosis, has been increasingly implicated in the pathogenesis of chronic inflammatory conditions, including cardiovascular, gastrointestinal, and autoimmune diseases, as well as metabolic disorders such as diabetes and obesity. A crucial mechanism through which the gut microbiota exerts its effects on host physiology is via the production of bioactive metabolites. These metabolites, including short-chain fatty acids, bile acids, and tryptophan derivatives, are key in modulating immune responses and regulating metabolic functions. Dysbiosis disrupts the production and function of these metabolites, thereby contributing to immune dysregulation, chronic inflammation, and disease progression. This review examines the role of gut microbiota-derived metabolites in chronic inflammatory diseases, with a focus on their immunomodulatory and metabolic effects. A deeper understanding of these mechanisms may open the way for novel therapeutic strategies aimed at restoring immune homeostasis and mitigating the global burden of chronic inflammatory diseases.